A comparative analysis of visual strategy in elite and amateur handball goalkeepers - Rivilla-Garcia, J.; Muñoz, A.; Grande, I.; Sanchis, M.; Sampedro, J. (Journal of Human Sport & Exercise, 2013)
The aim of the present study was to analyze the visual strategies prior to a throw from 7 metres in elite and amateur handball goalkeepers. To this end we analyzed the visual fixations in number and order of 10 goalkeepers (29.7±5.4 years; 14.7±8.6 years of experience), 3 elite and 7 amateurs, during the life size projection of 14 different throws, made by different players. During each throw the movement of the eyeballs, the dilation of the pupil (pupillometry) and the subject`s blinking were recorded thanks to a technological system which permitted eye tracking with high speed cameras, and the subsequent presentation of the visual data for each action studied. The elite goalkeepers performed a greater number of visual fixations than the amateur goalkeepers, revealing large and significant differences. Equally the priority zones observed were differed, with the amateur goalkeepers fixating more on the thrower`s face, and the elite goalkeepers paying more attention to the area of the arm/ball. It can therefore be inferred that elite goalkeepers have a greater perceptive capacity and also use different visual strategies from the amateur goalkeepers.